MULTIVITAMINS AND POLYUNSATURATED FATTY ACIDS IN THE TREATMENT OF ATTENTION DEFICIT HYPERACTIVITY DISORDER IN CHILDREN - L.M. Kuzenkova; L.S. Namazova; S.V. Balkanskaya; E.V. Uvakina (Union of pediatricians of Russia, 2009)
Therapeutic effect of Multi-tabs Intello Kids with Omega-3 and Multi-tabs Teenager has been assessed in the open controlled study included 70 patients with attention deficit hyperactivity disorder (ADHD), aged from 6 to 10 years . Group I and group II (20 +20 patients) received Multi-tabs Intello Kids with Omega-3/or Multi-tabs Teenager as a mono therapy of cognitive dis functions (СF) for 2 monthes. No pharmacological therapy was conducted in group of a control which included 30 patients with ADHD. Utilising the computer testing systems, basic of parameters CF were analyzed before and after the course of therapy. Statistically relevant positive effect of the vitaminis on cognitive functions was demonstrated.Key words: attention deficit hyperactivity disorder, therapy, multivitamins.